The Mouvement des Forces Démocratiques de Casamance: The Illusion of Separatism in Senegal? - (:unkn) unknown (My University, 2018)
On December 26, 1982, the Mouvement des Forces Démocratiques de Casamance (MFDC) voiced for the first time its demand for the independence of Casamance, the southern region of Senegal. This demand launched the longest, currently running violent conflict in Africa. The MFDC can thus lay claim to having led Africa’s second “secessionist moment” of the 1980s, after the first secessionist phase of the 1960s. Over the years, the Casamance conflict has killed several thousand people. It has been a discrete conflict though, with low-intensity violence and little of the extreme brutality that has made some African wars infamous. A peace process has been dragging on since 1991 and violence has waned. Over the past ten years, separatist guerrillas have been involved only in a handful of incidents. Has it all been an “illusory” separatism, as Englebert2 puts it, a bargaining chip for local elites trying to renegotiate the terms of their incorporation to the Senegalese state and appropriate local institutions? Can this hypothesis be reconciled with the duration of the conflict?
Keywords: African Research